The Role of Cloud Computing in Transforming ICT Infrastructure in Educational Institutions - Ibrahim, Umar (MultiTech Publisher, 2024)
The integration of cloud computing into the Information and Communication Technology (ICT) infrastructure of educational institutions is a transformative paradigm that holds significant implications for the efficiency and efficacy of academic processes. This paper explores the role of cloud computing in reshaping ICT infrastructure within educational settings. A comprehensive literature review establishes the current landscape of ICT in education, identifying challenges and limitations. The study delves into the theoretical foundations of cloud computing and investigates its potential benefits, including improved accessibility, scalability, and cost-effectiveness. Empirical evidence and case studies are presented to illustrate the transformative impact of cloud computing on educational ICT infrastructure. The discussion encompasses challenges and considerations, including data security and privacy concerns, and offers insights into the future directions of cloud computing in education. This research contributes to the ongoing dialogue surrounding technology in education and provides practical recommendations for harnessing the full potential of cloud computing.